Pengaruh Atresia Bilier Terhadap Perkembangan Fungsi Kognitif dan Motor pada Anak: Sebuah Tinjauan Sistematis - Theola, Jason; Jason, Jason; Catrawardhana, Prajnadiyan; Ashadi, Dhiya Athaullah Nurfateen; Oswari, Hanifah (Majalah Kedokteran Indonesia, 2023)
Introduction: Biliary atresia is the most common cause of progressive liver disease in children. Studies have shown that biliary atresia causes impairment of cognitive and motor development in children. This study was conducted to establish a systematic review that examines the relationship between biliary atresia and developmental disorders in children.Methods: Literature searching from electronic databases (PubMed, Cochrane, and SCOPUS) and hand searching were performed. Inclusion and exclusion criteria were applied to the selected studies. The selected studies were assessed for the risk of biases of each study. The results of each study were summarized and compared in a summary table.Result: A total of nine relevant studies were obtained from a systematic search through the electronic databases and external resources using specific keywords. Seven of nine studies reported that biliary atresia affects both children’s cognitive and motor development.Conclusion: Children with biliary atresia are generally suspected of having impaired cognitive and motor development. The relationship between surgical intervention in children with biliary atresia with cognitive and motor development in children is still unclear. Further studies are needed to determine the cognitive and motor development of children with biliary atresia before and after surgical intervention.